Modernisasi Pendidikan Islam: Studi Komparasi Pemikiran Muhammad Iqbal dan Fazlur Rahman - Sadewo, Barry Sandy; Sajari, Dimyati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research using qualitative method with a descriptive analysis approach. The type is library research by collecting and referring research based on primary and secondary sources, such as books, journals, or the other materials that are in line with the research topics. The result of this research there is the influence of the movement of thought by Continental Europe philosophy on Iqbal and Rahman. But, there are further differences in epistemology between they’re, Iqbal takes the path of existensialism which leads to individual human creativity, while Rahman takes the path of educational essentialism with the importance of Islamic intelletcuality as the key of educational renewal.